Odpowiedzi

2009-12-31T19:12:19+01:00
A)4przez x-3 -8=0
4/x-3 -8=0
[4-8(x-3)]/x-3=0/*(x-3)
4-8x+24=0
-8x=-28
x=28/8=7/2
b)2przez x-1 +3:x-2 -1=0
2/x-1 +3/x-2 -1=0
[2(x-2)+3(x-1)-(x-1)(x-2)]/(x-1)(x-2)=0/*(x-1)(x-2)
[2x-4+3x-3-x²+3x-2]=0
-x²+8x-9=0/*(-1)
x²-8x+9=0
Δ=64-36=28
√Δ=√28=2√7
x1=8-2√7/2=4-√7
x2=4+√7
c)4xprzez 2x-7=17
4x/2x-7=17/*2x-7
4x-17(2x-7)=0
4x-34x+119=0
-30x=-119/:30
x=119/30=3 29/30

d)4x-1:x =3x/*x
4x²-1=3x²
x²=1
x=-1 lub x=1
e)x+2:x=6/*x
x²-6x+2=0
Δ=36-8=28
√Δ=2√7
x1=6-2√7/2=3-√7
x2=3+√7
f)5- 4x-12:x =x/*x
5x-4x²-12-x²=0
-5x²+5x-12=0
Δ=25-240<0 brak rozwiązań
g)3:x-7 +6:5-8x=0
h)6x-7:2x-17=7
i)2:x-3 -x:2x+2 -5=0